Influence of academic procrastination on college students' mobile phone dependence： the pathways of cognitive emotion regulation strategies and anxiety - Yang Zimo; Gao Jiacheng; Ma Jiayi; Jiao Jiangli (Sichuan jingshen weisheng)
BackgroundIt has been shown that academic procrastination， cognitive emotion regulation strategies， anxiety and mobile phone dependence are closely related， but the detailed mechanism by which academic procrastination contributes to mobile phone dependence remains largely unclear and mediation analysis is currently lacking.ObjectiveTo explore the mediation role of cognitive emotion regulation strategies and anxiety in the relationship between academic procrastination and mobile phone dependence among college students， so as to provide references for the prevention and intervention of college students' mobile phone dependence.MethodsIn March 2023， 474 students from Xinjiang Normal University were selected by random sampling technique， and Mobile Phone Addiction Index （MPAI）， Procrastination Assessment Scale-Students （PASS）， Beck Anxiety Inventory （BAI） and Cognitive Emotion Regulation Questionnaire-Chinese version （CERQ-C） were used to conduct the survey. Pearson correlation analysis was adopted to examine the correlation among all variables， and Process 3.5 macro program was utilized to determine the mediation effect of cognitive emotion regulation strategies and anxiety on the relationship between academic procrastination and mobile phone dependence among college students.Results①PASS scores were positively correlated with the scores on CERQ-C negative cognitive emotion regulation strategy， BAI and MPAI （r=0.374， 0.229， 0.661， P<0.01）， CERQ-C negative cognitive emotion regulation strategy scores were positively correlated with BAI and MPAI scores （r=0.372， 0.498， P<0.01）， and BAI scores were positively correlated with MPAI scores （r=0.340， P<0.01）. ② Both negative cognitive emotion regulation strategy and anxiety exerted an mediation effect on the relationship between academic procrastination and mobile phone dependence among college students， with an effect value of 0.094 （95% CI： 0.056~0.137） and 0.013 （95% CI： 0.001~0.029）， and a chained mediation effect of negative cognitive emotion regulation strategy and anxiety on the relationship between academic procrastination and mobile phone dependence among college students was also documented， with an effect value of 0.015 （95% CI： 0.006~0.026）.ConclusionAcademic procrastination is proved to be effective in predicting college students' mobile phone dependence both directly and indirectly through either separate or chained mediation of negative cognitive emotion regulation strategy and anxiety. ［Funded by Social-Science Fund Project in Xinjiang （number， 2023CSH068）； Scientific Research Projects of Universities in Xinjiang Uygur Autonomous Region （number， XJEDU2023P081）］